Differences of adolescent career maturity in indonesia: a gender and job aspirations based approach - Verlanda Yuca; Uman Suherman; Amin Budiamin (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This article is a literature review related to career maturity. Career maturity is the maturity of attitudes and competencies in career decision making related to the suitability between individual career and behavior. This literature review aims to describe differences in student career maturity in terms of gender and job aspiration factors among adolescents in Indonesia. The method used in writing this article is a literature review, which is a search for both international and national literature that is carried out using the Google Scholar and Sciencedirect databases. The analysis used in this article uses descriptive analysis. The results of a literature review of empirical data found that there were differences in career maturity in terms of gender and job aspirations. This study will be useful in further research development, and also as reference material related to career maturity.